ISLAM DAN KESEJAHTERAAN MASYARAKAT : SIASAT USAHA PEDAGANG KAKI LIMA DENGAN PEMANFAATAN HUBUNGAN KOMUNITAS MUSLIM - mohammad syawaludin ibrahim (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2018)
The main subject of this research that is; Streer traders form a community and use it as a business tactics that make an important contribution to the value of their welfare. Including this section of research is to explain in depth the pattern of Muslim street traders community relationships and forms of community use as a business tactic. With the theory of parson structural functionalism in assisting with the social network theory of Luhkmanns and the value exchange theory of Homas, the framing of the relationship between the Muslim street traders community relationship with the value of benefit and welfare value is used to explain the activities of the social system and the daily activities of the street vendors. The results showed that the community of Muslim street vendors in the market Suak Bato Palembang as a form to respond challenging responses of uncertain market life both in terms of price stability and supply of merchandise. Relevance with the teachings of Islam shows a variety of practices and also related to the awareness of street vendors and the environment around him. Islamic narration practiced by Muslim street vendors among others; sincere behavior, keeping merchandise halal, barakah behavior, honest and fair and open behavior in scales.